2022
DOI: 10.2174/1568009622666220513094352
|View full text |Cite
|
Sign up to set email alerts
|

Netupitant-palonosetron (NEPA) for Preventing Chemotherapy-induced Nausea and Vomiting: From Clinical Trials to Daily Practice

Abstract: Chemotherapy-induced nausea and vomiting (CINV) is a common adverse event associated with many anticancer therapies and can negatively impact patients' quality of life and potentially limit the effectiveness of chemotherapy. Currently, CINV can be prevented in most patients with guideline-recommended antiemetic regimens. However, clinicians do not always follow guidelines, and patients often face difficulties adhering to their prescribed treatments. Therefore, approaches to increase guideline adherence need to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 65 publications
(171 reference statements)
0
7
0
Order By: Relevance
“…Severity of nausea assessment also reported, NSN (≤25 mm) in 92.38% (n = 327) patients, with 77.97% (n = 276) patients reporting no nausea. The NSN was 60-78% in other real-world studies with NEPA [ 15 , 16 ]. The conventional oral anti-emetic regimen containing aprepitant resulted in no significant nausea in 70-73% of patients, as reported in three randomized controlled trials with cisplatin-based regimens [ 17 - 19 ] and 61% in an anthracycline and cyclophosphamide-based regimen study [ 20 ].…”
Section: Discussionmentioning
confidence: 78%
“…Severity of nausea assessment also reported, NSN (≤25 mm) in 92.38% (n = 327) patients, with 77.97% (n = 276) patients reporting no nausea. The NSN was 60-78% in other real-world studies with NEPA [ 15 , 16 ]. The conventional oral anti-emetic regimen containing aprepitant resulted in no significant nausea in 70-73% of patients, as reported in three randomized controlled trials with cisplatin-based regimens [ 17 - 19 ] and 61% in an anthracycline and cyclophosphamide-based regimen study [ 20 ].…”
Section: Discussionmentioning
confidence: 78%
“…A posthoc pooled analysis of phase 3 study conducted by Aapro et al demonstrated that NEPA when received orally had significant superiority in nausea control during the delayed and overall periods compared with palonosetron in the cisplatin and Doxorubicin and Cyclophosphamide (AC) based settings and a considerable advantage compared with aprepitant-based regimens in non-AC-based HEC [ 15 ]. Three pivotal, multicentre, randomized, double-blind and registration studies focusing on cisplatin-based highly HEC, who either received a single oral dose of NEPA plus dexamethasone before chemotherapy or aprepitant-based regimen (APR), showed delayed phase had notable differences in response rates between patients treated with NEPA plus dexamethasone and those receiving APR, 5-HT3RA, and dexamethasone.…”
Section: Discussionmentioning
confidence: 99%
“…This activation signals the abdominal muscles, diaphragm, and stomach to trigger emesis via stimulating the dorsal vagal complex comprising the vomiting center. 2,3 Therefore, inhibiting both 5HT-3 and NK 1 receptors simultaneously can effectively reduce both acute and delayed CINV. International guideline committees also recommend the use of a combination of antiemetic drugs that target various molecular pathways linked to emesis as the established standard of care for preventing CINV.…”
Section: Introductionmentioning
confidence: 99%
“…Chemotherapy-induced nausea and vomiting (CINV) is a complex condition that can have a detrimental effect on a patient's health, causing electrolyte imbalance, dehydration, and malnutrition that can result in challenges with adherence to therapy, ultimately leading to suboptimal cancer treatment. 1 2 Based on the occurrence of the emesis, CINV is categorized into acute and delayed phases. Acute CINV triggers within 24 hours of the commencement of chemotherapy predominantly by serotonin release from enterochromaffin cells within the gastrointestinal tract.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation